The razor's edge - Maugham, W. Somerset (William Somerset), 1874-1965. (New York : Penguin Books, 1992)
A young American man named Larry Darrell traverses Europe, China, Burma, and India in search of meaning after experiencing the horrors of the First World War.
First published: 1944.
Includes bibliographical references (p. xxv-xxvii).
Adult.
Adult
Keywords: Americans -- Fiction; God -- Fiction; World War, 1914-1918 -- Veterans -- Fiction; Americans -- Fiction; Bildungsromans; God -- Fiction; Veterans -- United States -- Fiction; India -- Fiction; Paris (France) -- Fiction; India -- Fiction; Paris (France) -- Fiction; Bildungsromans